Song of the Vikings : Snorri and the making of the Norse myths - Brown, Nancy Marie (Palgrave Macmillan, 2012)
"Much like Greek and Roman mythology, Norse myths are read, reread, and treasured. Famous storytellers such as JRR Tolkien and Neil Gaiman have drawn their inspiration from the long-haired, mead-drinking, marauding and pillaging Vikings. The author who gave us Nordic mythology is a twelfth-century Icelandic chieftain by the name of Snorri Sturluson. Like Homer, Snorri was a bard, writing down and embellishing the folklore and pagan legends of medieval Scandinavia. While his stories make great reading for children, the amazing world of medieval Scandinavia has been omitted from narrative history. In Song of the Vikings, award-winning author Nancy Marie Brown brings to life the intrigue and power struggles at the court of medieval Reykjav'k that Snorri inhabited. Drawing on new and original research, her deep knowledge of Icelandic history, and first-hand reading of the original medieval sources, Brown produces a richly textured narrative of a world that continues to fascinate. "--